ANALISIS KONSEP DIRI POSITIF PADA SISWA KELAS XI SMK MUHAMMADIYAH 1 KABUPATEN KUBU RAYA - Tirta Relieyana; Muhammad Asrori; Purwanti Purwanti (Universitas Tanjungpura, 2021)
AbstrakA person's self-concept is his point of view and attitude towards himself. To maximize their potential, students are required to have a positive self-concept, especially in areas related to learning, so as to increase interest in learning and improve learning achievement.Quantitative methods are used in this study. Questionnaires are used in conjunction with indirect communication strategies and data collection technologies to collect information. The % formula is used in the analytical approach, on the other hand. A good self-concept is found in class XI students of SMK Muhammadiyah 1 according to the findings of this study. The actual score was 2758, compared to the maximum possible perfect score of 3456, which puts students at 80 percent in the